2020
DOI: 10.5115/acb.19.241
|View full text |Cite
|
Sign up to set email alerts
|

Role of cerebrospinal fluid in differentiation of human dental pulp stem cells into neuron-like cells

Abstract: Human dental pulp stem cells (hDPSCs) could be differentiated into neuron like-cells under particular microenvironments. It has been reported that a wide range of factors, presented in cerebrospinal fluid (CSF), playing part in neuronal differentiation during embryonic stages, we herein introduce a novel culture media complex to differentiate hDPSCs into neuron-like cells. The hDPSCs were initially isolated and characterized. The CSF was prepared from the Cisterna magna of 19-day-old Wistar rat embryos, embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The same group has recently published a letter suggesting the potential of using neural crest-derived stem cells from hair follicles in Parkinson's disease treatment, thanks to their ability to generate dopaminergic neurons as a response to eCSF presence (Pandamooz et al, 2022). A similar effect on neuronal differentiation was presented in a study in which human dental pulp stem cells (hDPSCs) were investigated (Goudarzi et al, 2020). This research showed, that CSF isolated from the cisterna magna of 19-dayold Wistar rat embryos added to the culture even for 2 days can induce final differentiation to neuron-like cells from hDPSCs, resulting in expression of Nestin, MAP2 and the presence of Nissl bodies in the cytoplasm (Table 2).…”
Section: Effect Of Csf On Other Cell Typesmentioning
confidence: 89%
“…The same group has recently published a letter suggesting the potential of using neural crest-derived stem cells from hair follicles in Parkinson's disease treatment, thanks to their ability to generate dopaminergic neurons as a response to eCSF presence (Pandamooz et al, 2022). A similar effect on neuronal differentiation was presented in a study in which human dental pulp stem cells (hDPSCs) were investigated (Goudarzi et al, 2020). This research showed, that CSF isolated from the cisterna magna of 19-dayold Wistar rat embryos added to the culture even for 2 days can induce final differentiation to neuron-like cells from hDPSCs, resulting in expression of Nestin, MAP2 and the presence of Nissl bodies in the cytoplasm (Table 2).…”
Section: Effect Of Csf On Other Cell Typesmentioning
confidence: 89%
“…Interestingly, the cerebrospinal fluid (CSF) also provided a favorable microenvironment for differentiating hDPSCs into neurogenic lineages (Goudarzi et al, 2020 ). As the CSF is in direct contact with NSCs in the CNS, it contains neurotrophic and growth factors with other nutrients and cytokines, which are able to induce neural differentiation of hDPSCs with the simultaneous usage of RA.…”
Section: Neural Differentiationmentioning
confidence: 99%
“…The process of identifying viable sources of neural progenitor cells from various sources, to promote neurogenesis post CNS injury. Recent studies have also identified human dental pulp stem cells as a promising candidate for stem cell therapy as they differentiate in to neuron like cells [ 44 , 45 ]. These stem cells were derived from ectomesenchyme neural crest, which means they have the similar characteristic to that of mesenchymal and neural crest stem cells [ 45 , 46 ].…”
Section: Properties Of Neural Progenitor Cellsmentioning
confidence: 99%